2022
DOI: 10.1093/cid/ciac169
|View full text |Cite
|
Sign up to set email alerts
|

Antibody Response in Immunocompromised Patients After the Administration of Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) Vaccine BNT162b2 or mRNA-1273: A Randomized Controlled Trial

Abstract: Background BNT162b2 by Pfizer-BioNTech and mRNA-1273 by Moderna are the most commonly used vaccines to prevent SARS-CoV-2 infections. Head-to-head comparison of the efficacy of these vaccines in immunocompromised patients is lacking. Methods Parallel, two-arm (allocation 1:1), open-label, non-inferiority randomised clinical trial nested into the Swiss HIV Cohort Study and the Swiss Transplant Cohort Study. Patients living wit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 17 publications
1
20
0
Order By: Relevance
“…Hence, nuanced assessment of antibody development to SARS-CoV-2 vaccines is critical for understanding the most important determinants of humoral immune response and for protecting patients at risk of not developing adequate vaccine response. In this post hoc analysis of our trial data [3], we investigated factors that influence the antibody response to both mRNA vaccines in people with HIV (PWH).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, nuanced assessment of antibody development to SARS-CoV-2 vaccines is critical for understanding the most important determinants of humoral immune response and for protecting patients at risk of not developing adequate vaccine response. In this post hoc analysis of our trial data [3], we investigated factors that influence the antibody response to both mRNA vaccines in people with HIV (PWH).…”
mentioning
confidence: 99%
“…Following the approval of Pfizer-BioNTech (BNT162b2; Comirnaty) and Moderna (mRNA-1273; Spikewax) vaccines against severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) by Swiss health authorities, the Swiss HIV Cohort Study (SHCS) [1] and the Swiss Transplant Cohort Study (STCS) rapidly joined forces and built a trial platform embedded in the two cohorts [2,3] that monitors vaccine efficacy and investigates the antibody response in immuno-compromised patients. The continuous emergence of divergent variants requires increased antibody titers to establish vaccine efficacy [4][5][6].…”
mentioning
confidence: 99%
“…Of the 430 patients, 412 could be included into the intention-to-treat dataset for the main analysis, i.e., comparing the two vaccines. The results of this pilot study, including detailed characteristics of the study population, were published on March 2nd 2022 [ 26 ]. In addition, data collected in the COVERALL pilot trial were merged back to data collected in the SHCS.…”
Section: Resultsmentioning
confidence: 99%
“…[ 47 ] However, several studies have shown that PLWH receiving two doses of mRNA-1273 have a greater neutralizing humoral response than PLWH receiving two doses of BNT162b2. [ 38 , 48 , 49 ] Moreover, a recent study described a higher risk of SARS-CoV-2 breakthrough in PLWH with BNT162b2 (Pfizer-BioNTech), with an increased risk of breakthroughs of 2.6% and 1.7% for mRNA BNT162b2 and mRNA-1273 vaccines, respectively, in PLWH than in HIV-uninfected individuals. [ 50 ] Among PLWH, the cumulative incidence and relative risks of breakthroughs were not significantly different based on CD4 + T cell count or HIV viral load suppression.…”
Section: Overview Of Sars-cov-2 Vaccination In Plwhmentioning
confidence: 99%